Large-Scale Investigation of Base Excision Repair Genetic Polymorphisms and Lung Cancer Risk in a Multicenter Study - Hung, Rayjean J.; Brennan, Paul; Canzian, Federico; Szeszenia-Dabrowska, Neonila; Zaridze, David; Lissowska, Jolanta; Rudnai, Peter; Fabianova, Eleonora; Mates, Dana; Foretova, Lenka; Janout, Vladimir; Bencko, Vladimir; et al. (JNCI : Journal of the National Cancer Institute, 2005)
Background: Base excision repair (BER) is a highly conserved essential mechanism for maintaining genome integrity. We examined associations among four well-characterized polymorphisms of BER genes (OGG1 Ser326Cys, XRCC1 Arg194Trp, XRCC1 Arg280His, and XRCC1 Arg399Gln) and lung cancer risk. Methods: A total of 2188 patients with lung cancer and 2198 control subjects without lung cancer recruited at 15 centers in six Eastern European countries from February 1998 to October 2002 provided DNA samples for genotype analysis. Genetic polymorphisms were analyzed by the fluorescence 5′ exonuclease and Amplifluor assays. Unconditional multivariable logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs). We estimated the false-positive reporting probability (FPRP) for our results by incorporating a range of prior probabilities that specific polymorphisms are associated with lung cancer risk. All statistical tests were two-sided. Results: The overall odds ratio for lung cancer among those with the OGG1 Cys/Cys genotype compared with those with the OGG1 Ser/Ser genotype was 1.34 (95% CI = 0.95 to 1.88); the association was most prominent for adenocarcinoma risk (OR = 1.66, 95% CI = 1.04 to 2.66). Overall, the XRCC1 polymorphisms were not associated with the risk of lung cancer. However, the XRCC1 Arg194Trp and Arg280His variants were each associated with a reduced risk of lung cancer among subjects in the highest quartile of pack-years of smoking compared with common allele homozygotes (ORs of 0.65 [95% CI = 0.46 to 0.93] and 0.56 [95% CI = 0.36 to 0.86], respectively). The associations between the OGG1 Cys/Cys genotype and adenocarcinoma risk and between XRCC1 Arg194Trp polymorphism and lung cancer risk among heavy smokers remained robust given prior probabilities of 25% (FPRP = 0.238) and 10% (FPRP = 0.276), respectively. Conclusions: Our results do not support a major independent role of BER gene polymorphisms in lung cancer risk. However, we cannot exclude the possibility that the OGG1 Ser326Cys and XRCC1 Arg194Trp polymorphisms play minor roles in lung carcinogenesis.